2017
DOI: 10.1007/s12088-017-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Phlorotannins from Edible Brown Algae, Eisenia bicyclis Against Streptomycin-Resistant Listeria monocytogenes

Abstract: (LM) is an important food borne pathogen responsible for listeriosis. Further, LM is an etiological agent associated with life threatening conditions like meningitis and encephalitis. Biofilm forming and drug resistant LM may potentially become difficult to treat infections and hence effective controlling measures are required to prevent LM infections. In view of this, the present study evaluated an anti-listerial potential of edible brown seaweed, , by disc diffusion and micro-dilution methods. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…In line with our results, the study conducted by Machu et al (2015) disclosed the highest antioxidant capacity adopting the water extraction for brown algae. Machu et al (2015) tested Eisenia bicyclis that is a brown alga rich in phlorotannins that revealed also antimicrobial capacities against streptomycin resistant Listeria monocitogenes (Kim et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In line with our results, the study conducted by Machu et al (2015) disclosed the highest antioxidant capacity adopting the water extraction for brown algae. Machu et al (2015) tested Eisenia bicyclis that is a brown alga rich in phlorotannins that revealed also antimicrobial capacities against streptomycin resistant Listeria monocitogenes (Kim et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…F. vesiculosus produced the best inhibition, IC 50 was 2.24 mg/mL ( E. coli ) and 1.27 mg/mL ( S. aureus ). Despite preliminary results showed that different species of algae have an antimicrobial potential especially against E. coli and S. aureus [ 33 , 34 , 35 ], there are no many studies about the antibacterial activity of seaweeds used in the present study. El-Amraoui and co-workers evaluated the antimicrobial activity of several macroalgae extracts from the Maroccan Atlantic Coast [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors recommended these extracts as an antibacterial preparation against S. aureus , a common causative agent of foodborne toxicoinfections that are accompanied by vomiting, diarrhea, and intestinal spasms [ 122 ]. This bacterium also causes spoilage of meat, including poultry, dairy products, salads, shrimp, and ham [ 123 ]. The extracts have not only antibacterial but also antioxidant effects, suggesting their use as an effective food preservative in an appropriate combination.…”
Section: Importance Of Marine Algal Polyphenols As Food Preservatimentioning
confidence: 99%
“…H.J. Kim et al [ 123 ] established the anti-listerial effect of phlorotannins isolated from the alga E. bicyclis . Extraction and purification of compounds are carried out, as described.…”
Section: Importance Of Marine Algal Polyphenols As Food Preservatimentioning
confidence: 99%
See 1 more Smart Citation